2008
DOI: 10.1212/01.wnl.0000313034.46883.16
|View full text |Cite
|
Sign up to set email alerts
|

Disability as an outcome in MS clinical trials

Abstract: Clinical surrogates of unremitting disability used in trials of relapsing-remitting multiple sclerosis cannot be validated. Trials have been too short or degrees of disability change too small to measure the key outcomes. These analyses highlight the difficulty in determining effectiveness of therapy in chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 30 publications
5
122
0
1
Order By: Relevance
“…Thus, short-term increases in EDSS do not necessarily predict future accumulation of disability in RMS patients over the longer term, a conclusion also reached in a pooled analysis of patients randomized to placebo arms in 31 clinical trials. 48 Because neither clinical nor radiographic features over two years had predictive value, it is not surprising that the combined measure of these variables, NEDA, was also not associated with long-term disability risk. Although this observation must be interpreted with caution because of the relatively small number of NEDA patients in our cohort, another recently published observational study also found that the proportion of patients meeting a NEDA definition declined substantially over time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, short-term increases in EDSS do not necessarily predict future accumulation of disability in RMS patients over the longer term, a conclusion also reached in a pooled analysis of patients randomized to placebo arms in 31 clinical trials. 48 Because neither clinical nor radiographic features over two years had predictive value, it is not surprising that the combined measure of these variables, NEDA, was also not associated with long-term disability risk. Although this observation must be interpreted with caution because of the relatively small number of NEDA patients in our cohort, another recently published observational study also found that the proportion of patients meeting a NEDA definition declined substantially over time.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in MRI T2 lesion volume and new lesions were also observed. Notably, this was one of the first trials to employ time to confirmed disability as an outcome [34,35]. Because the EDSS is poorly responsive to changes in the 6-6.5 range, this group also employed a different definition of EDSS change in that range of just 0.5 points, a trend that persists in MS research.…”
Section: Progressive Formsmentioning
confidence: 99%
“…[16][17][18] Furthermore, even sustained EDSS progression in research studies may reverse after study completion. 19 enhancing (Gd+) T1-weighted lesions or unequivocally new or enlarging T2-weighted lesions. Although this poll reflected the opinions of a relatively small proportion of the CMSC membership over a short period of time, the results supported the concept that changes to the Lublin-Reingold classification should be considered.…”
Section: Historical Analysis and Critique Of The Lublinreingold Criteriamentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48] In considering the histologic characteristics of classic MS MRI lesions, it is important to recognize that when frequent, sensitive longitudinal (weekly or monthly) 37,49 MRI studies are performed in RRMS patients, almost both relapsing and progressive forms of MS 18,19,31 ; the EDSS is a relatively insensitive barometer of progression; and pseudoprogression may occur, making it difficult to accurately assess stability, worsening, or even mild improvement over the short term. 16,17,19 Progression of cognitive dysfunction is more problematic to clearly document, by either routine clinical or routine imaging metrics. Mild-to-moderate cognitive impairment may not be readily detected even by competent physicians or on EDSS testing, which is insensitive to such changes, [16][17][18] nor can cortical gray matter lesions be easily detected with conventional MRI techniques.…”
Section: Relationship Of Mri To Cns Pathologymentioning
confidence: 99%
See 1 more Smart Citation